Hey there!
Let's do this step by step:
1. P-13=2 -------Write out the equation
2. P-13+13=-2+13 ------- Undo the operations
3.
![\frac{p}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bp%7D%7B1%7D%20)
=
![\frac{11}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B11%7D%7B1%7D%20)
------- What you get
4. P=11
(If you feel that my answer has helped you, please consider rating it and giving it a thank you! Also, feel free to make the best answer, the brainliest answer!)
<span>Thank you for being part of the brainly community! :D</span>